Modern assemblages of benthic foraminifera in the Zhitkov Bay (Russky Island) of Peter the Great Bay, Japan Sea - Tatyana S. Tarasova; Alexandra V. Romanova; Sergey P. Pletnev; Vladimir K. Annin (Известия ТИНРО, 2016)
Taxonomic and quantitative composition of Foraminifera assemblages in the Zhitkov Bay (Russky Island, Peter the Great Bay, Japan Sea) are described. In total, 52 species from 30 genera and 14 families of benthic foraminifera have been identified in bottom sediments. The most of them are represented by calcareous forms (38 species), with the highest abundance of families Elphidiidae, Discorbidae, and Buliminidae, other are 14 species of agglutinated foraminifera, including 2 common species of families Trochamminidae and Ataxophragmiidae. Population density of benthic foraminifera correlates well with the type of bottom sediments: the highest abundance is observed on alenric sediments and pebble-sandy grounds and the lowest abundance - on fine-grained pelitic sediments. Six assemblages of benthic foraminifera are determined for the Zhitkov Bay, taking into account the prevailing families.